A7.6 Neuropathic pain in rheumatic diseases: a cross-sectional study. (31st January 2014) - Meirinhos, T; Aguiar, R; Ambrósio, C; Barcelos, A
Abstract : Introduction: Pain is the most common symptom in rheumatic diseases. In its pathophysiology there is usually a disturbance in nociceptive perception by tissue damage, that evolve often to features of central pain, with characteristics of neuropathic pain (NP). Neuropathic pain in rheumatic diseases is a topic rarely addressed in the literature. Objectives: Determine, in a cohort of patients with rheumatoid arthritis (RA), osteoarthritis (OA) axial (a-SpA) and peripheral (p-SpA) spondylarthritis, the prevalence of DN, correlations between NP and activity and disease duration. Compare the prevalence of DN with control group. Materials and Methods: Cross-sectional study. Variables analysed: sex, age, duration of illness, medication. All patients answered VAS of pain, DN4 and EQol-5D. In patients with RA and p-SpA we determined DAS28, BASDAI and BASFI in a-SpA and WOMAC in OA. Control group of healthy subjects randomised with patients in age and sex responded DN4. Statistical analysis using SPSS 18. Results: 216 patients enrolled (80RA, 48p-SpA, 46a-SpA, 42OA), 85 men and 131 women, with mean age 55.27 ± 14.62 years, mean disease duration 10 ± 11.87years. 48patients had ≥4 DN4, only 3 were on medication to NP. The NP prevalence was 40.47% in OA (p < 0.01), 18.75% RA, 23.91% a-SpA and 10:42% p-SpA. The prevalence of DN was higher in patients compared with controls, in OA (OR = 23.12% CI 95 (2.88–185.41) and SPA´s (OR = 8.62 CI 95% (1.1–67.25). Despite the increasing prevalence of DN with duration of disease, this difference was not statistically significant. Regarding disease activity, we found that DN increases with BASDAI (p < 0:02) in a-SpA and DAS28 in RA (p < 0.02). Higher values ​​of VAS were found in patients with DN4 ≥4 (p < 0.001). Conclusion: This study reveals an important neuropathic component in our cohort of patients. The disease with the highest prevalence of DN was OA, which meets the data found in the literature. This discrepancy in prevalence, lower in inflammatory conditions, though chronic, certainly needs further study, placing the use of more aggressive therapy in these patients, like DMARD's, as a plausible hypothesis. This study demonstrates the need for a better understanding of the mechanisms and types of pain in rheumatic patients, with nociceptive pain only part of the spectrum of pain. Additional studies are needed to investigate the importance of neuropathic pain in rheumatic diseases, and its relation with the evolution of the underlying disease.